Bastard or Playmate? Adapting Theatre, Mutating Media and Contemporary Performing Arts - Vanderbeeken, Robrecht; Debackere, Boris; Depestel, David; Stalpaert, Christel (Theater Topics, 2012)
Artistic media seem to be in a permanent condition of mutation and transformation. Contemporary artists often investigate the limits and possibilities of the media they use and experiment with their crossing, upgrading and mutilation. Others explicitly explore the unknown space between existing media, searching for the hybrid beings that occupy these in-betweens. This fascinating volume explores the theme of mutating and adapting media in its relation to theatre and performance. How did different aspects of theatre evolve in a digital era? How did historical traditions in theatre adapt to new cultural contexts? How are other media remediated in contemporary performances? Does this eventually lead to a contamination or even a disintegration of what we call theatre, or on the contrary, to a revaluation? Bringing together international scholars and artists, the editors offer a comprehensive overview of the subject sensitive to the cross-disciplinary use of key concepts such as remediation, digitization, interactivity, corporeality, liveness, surveillance, spectacle, performativity and theatricality. The book guides readers new to the area of intermediality, as well as experienced researchers into one of the most dynamic fields of scholarship.